FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PELAPORAN PERTANGGUNGJAWABAN KOTA PAREPARE - Widya Ulandari; Syarifuddin Yusuf (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the factors that influence the delay in reporting the accountability of the City of Parepare. The method used in this study is quantitative. The sampling technique in this study was total sampling. Total sampling is a sampling technique where the number of samples is equal to the population of 46 populations. The results showed that only one variable, namely the capacity of Human Resources (HR), affected the delay in reporting accountability. Variable use of information technology and the Internal Control System (SPI) have no effect on delays in reporting accountability. Timeliness indicates that financial statements must be presented within a predetermined period of time to show the extent of the implementation of the SKPD APBD. The delay in the accountability of one of the agencies will hamper the process of preparing the financial statements of the City of Parepare.